Behavioral Roadmap: Linking Micro Assessments and Macro Change in Social Well-Being - Yurnalia, Anita; Yuliyantini, Yuliyantini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study positions human behavior at the core of social welfare practice, showing how cognitive (beliefs and judgments), affective (emotions and relatedness), and conative (intentions and volition) processes translate into social functioning across micro meso macro contexts. Through a structured literature review, it synthesizes evidence that attitudes, perceived norms, and perceived control shape intentions and, when supported by self-efficacy, modeling, feedback, and social support, increase adherence, participation, and persistence. The analysis integrates ecological perspectives, emphasizing the role of families, peer networks, service organizations, and policy arrangements in enabling or constraining action by altering information, time, and administrative costs. It proposes a cross-disciplinary framework linking assessment, intervention, and evaluation: assess specific beliefs, emotions, perceived barriers, and stage of change; design multi-level strategies that combine targeted education, skills practice, peer support, and procedural simplification; and monitor proximate indicators (intention, self-efficacy, perceived control, and barriers) alongside administrative outputs. By aligning individual goals with system change such as reducing administrative burden, offering low-cost reminders, and strengthening community partnerships the framework lowers structural frictions and normalizes prosocial choices. The result is a pragmatic, context-sensitive pathway for social workers to foster durable behavior change while safeguarding equity and dignity.